Research in the social scientific study of religion. - Piedmont, Ralph L., 1958-; Village, Andrew. (Research in the Social Scientific Study of Religion, 2014)
The 25th volume of Research in the Social Scientific Study of Religion continues to provide readers with an interdisciplinary assortment of high quality research studies aimed at capturing salient, contemporary trends in the field. The current volume presents a special section examining the role of spiritual and religious themes in sexuality research. Engaging analyses evaluate homonegativity and how religious advocacy influences perceptions of gay and lesbian individuals across different cultures. Also included are papers on the development of sexual identities among religious committed individuals. These papers help to connect concepts too frequently considered unrelated. The regular articles provide similarly stimulating evaluations of timely topics such as religious coping, gratitude, and the role of personality in describing religious experiences.